Dissimilarity of Ant Communities Increases with Precipitation, but not Reduced Land-Use Intensity, in Indonesian Cacao Agroforestry - Damayanti Buchori; Teja Tscharntke; Yann Clough; Akhmad Rizali (Diversity, 2013)
Land-use degradation and climate change are well-known drivers of biodiversity loss, but little information is available about their potential interaction. Here, we focus on the effects of land-use and precipitation on ant diversity in cacao agroforestry. In Central Sulawesi, Indonesia, we selected 16 cacao agroforestry plots with a shaded vs. unshaded plot in each of eight villages differing in precipitation (1032–2051 mm annual rainfall). On each plot, 10 cacao trees with similar size and age (7–10 years) were selected for hand collection of ants on each cacao tree and the soil surface. In total, we found 80 ant species belonging to five subfamilies. Land-use intensification (removal of shade trees) and precipitation had no effect on species richness of ants per cacao tree (alpha diversity) and, in an additive partitioning approach, within-plot beta diversity. However, higher precipitation (but not shade) significantly increased ant species dissimilarity across cacao trees within a plot, with ant species showing contrasting responses to precipitation. Reduced precipitation causing drought stress appeared to contribute to convergence of ant community structure, presumably via reduced heterogeneity in cacao tree growth. In conclusion, reduced precipitation greatly influenced ant community dissimilarity and appeared to be more important for ant community structure than land-use intensification.